STUDIES ON THE VIRUSES OF ENTAMOEBA HISTOLYTICA: A PROGRESS REPORT - MATTERN CF; HRUSKA, JF; DIAMOND, LS (INST MEXICANO SEGURO, SOCIAL APDO POSTAL 73-032, MEXICO D F 03020, MEXICO, 1972)
Nine strains of E. histolytica and one strain of E. hartmanni were examined for the presence of indigenous viruses. Each of the histolytica strains was isolated from a patient suffering acute disease. Represented in the collection are isolates from rectal
ARCH INVEST MED
Keywords: antiserum, animal, article, chick embryo, classification, cytopathogenic effect, embryo, Entamoeba histolytica, growth, development and aging, mouse, virus, virus culture, Animal, Chick Embryo, Cytopathogenic Effect, Viral, Embryo, Entamoeba histolytica; CIENCIAS MEDICAS; OTRAS ESPECIALIDADES MEDICAS (ESPECIFICAR); VIROLOGIA MEDICA